Analisa Yuridis Putusan Pernikahan Beda Agama Ditinjau Dari Undang-Undang No 1 Tahun 1974 - B, Muh Rivai; Iskandar, Hardian (Fakultas Syariah INSURI Ponorogo, 2023)
Religious weddings in Indonesia have been a difficult and tangled matter of legal debate. This study intends to produce legislation that governs themes the author discusses in light of current instances via this article, which applies normative research methodologies to solve its difficulties. The documentation of the legitimacy of interreligious weddings needs more legal assurance. Although Marriage Law No. 1 of 1974 makes it lawful, there still needs to be more work with administrative records under Population Act No. 24 of 2013, which enables opportunities for couples who may join in weddings of various faiths. Marriage between a Muslim and a non-Muslim is prohibited in Islamic law, according to Rule 40 of the Islamic Law Compilation, unless otherwise approved by relevant legislation. Article 2(1) of Marriage Act No. 1 of 1974 prohibits marriage between a Muslim and a non-Muslim. Interreligious couples must be given the same legal status and the same right to build a family via marriage under the 1945 Constitution and Law No. 39 of 1999 on Human Rights. In contrast, the Supreme Court of Indonesia issued letter 2 of 2023, urging judges not to stop interfaith marriage immediately. This essay highlights how difficult it is to attain legal clarity and certainty—better laws and policies and more exact legal interpretations.